Kinematic analysis and synthesis of a compound epicyclic gear mechanism with intermeshing satellites - Bozherikov, Sylvester; Tsoneva, Mina; Uzunov, Hristo; Dechkova, Silvia (Zielona Góra: Uniwersytet Zielonogórski)
In the present work, a study has been conducted on the possible kinematic configurations of a given gear mechanism with intermeshing satellites to compare the values of the transmitted torques. As a result of this analysis, principal schemes of compound epicyclic gear mechanisms achieving high values of transmitted torques at the output have been proposed. Kinematic synthesis of the mechanisms with optimal gear ratios achieving the highest values of output torques has been performed.
Keywords: epicyclic gear mechanism; differential mechanism; planetary mechanism; satellites; kinematic scheme